The Invisibility of Violence: A Necropolitical Analysis of the National Inquiry's Final Report on Missing and Murdered Indigenous Women and Girls (MMIWG) - Purba, Gurbani (Université d'Ottawa / University of Ottawa, 2025)
The National Inquiry's Final Report (2019) into the Missing and Murdered Indigenous Women and Girls represents one of the first comprehensive national studies that examines the acts of state-based genocide against Indigenous women and girls. The goal of this thesis is to investigate the findings of the National Inquiry to present a necropolitical insight into the heightened experiences of violence and death that affect Indigenous women and girls. Using a theoretical lens of necropolitics, as developed by Mbembe, and other scholars, this thesis provides an analysis of the National Inquiry's Final Report to see how the state is involved in the politics of death in the lives of Indigenous women and complicit in the violence against them. Where the National Inquiry made the state, practitioners, and the public responsible for addressing the murders and disappearances, this thesis highlights the limitations in this recommendation because, from a theoretical lens of necropolitics, violence, and death are inherent activities of the state. This thesis leads the path forward to welcome future research that envisions the need for community options outside of state-based operations in connecting and building community capacity.
Keywords: Necropolitics; Violence; Missing and murdered Indigenous women; Mbembe; National Inquiry; Indigenous women; Thematic analysis; Colonialism; Systemic violence; Biopolitics